Swift heavy ion induced formation of Al/polymer composite layer for low thermal emissivity in the IR range - Babrekar, Harshada A.; Jog, Jyoti Prakash; Mathe, Vikas L.; Avasthi, D. K.; Ojha, S.; Bhoraskar, S. V. (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions with Materials and Atoms, 2012)
Composites of polymers with aluminium were formed by swift high energy ions of 150 MeV, which are used as low thermal emissivity materials for infrared wavelengths between 8-14 mu m. Emissivity and dielectric constants were studied for these structures. A semi-empirical model has been established to obtain the relation between emissivity and dielectric constant. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: composites; dielectric constant; Swift heavy ion; Thermal emissivity